Mycobacterium leprae Recombinant Antigen Induces High Expression of Multifunction T Lymphocytes and Is Promising as a Specific Vaccine for Leprosy - Bezerra-Santos, Márcio; do Vale-Simon, Marise; Barreto, Aline Silva; Cazzaniga, Rodrigo Anselmo; de Oliveira, Daniela Teles; Barrios, Mônica Rueda; Ferreira, Alex Ricardo; Santos-Bio, Nanci C.; Reed, Steven G.; de Almeida, Roque Pacheco; Corrêa, Cristiane Bani; Duthie, Malcolm S.; et al. (Frontiers in Immunology, 2018)
Leprosy is a chronic disease caused by M. leprae infection that can cause severe neurological complications and physical disabilities. A leprosy-specific vaccine would be an important component within control programs but is still lacking. Given that multifunctional CD4 T cells [i.e., those capable of simultaneously secreting combinations of interferon (IFN)-γ, interleukin (IL)-2, and tumor necrosis factor (TNF)] have now been implicated in the protective response to several infections, we tested the hypothesis if a recombinant M. leprae antigen-specific multifunctional T cells differed between leprosy patients and their healthy contacts. We used whole blood assays and peripheral blood mononuclear cells to characterize the antigen-specific T cell responses of 39 paucibacillary (PB) and 17 multibacillary (MB) leprosy patients and 31 healthy household contacts (HHC). Cells were incubated with either crude mycobacterial extracts (M. leprae cell sonicate–MLCS) and purified protein derivative (PPD) or recombinant ML2028 protein, the homolog of M. tuberculosis Ag85B. Multiplex assay revealed antigen-specific production of IFN-γ and IL-2 from cells of HHC and PB, confirming a Th1 bias within these individuals. Multiparameter flow cytometry then revealed that the population of multifunctional ML2028-specific T cells observed in HHC was larger than that observed in PB patients. Taken together, our data suggest that these multifunctional antigen-specific T cells provide a more effective response against M. leprae infection that prevents the development of leprosy. These data further our understanding of M. leprae infection/leprosy and are instructive for vaccine development.